UMP to expand collaboration with LiuZhou Railway Vocational Technology College in the field of Engineering and Railway Technology - Mimi Rabita, Abdul Wahit (2023)
PEKAN, July 11, 2023 - A visit by a delegation from LiuZhou Railway Vocational Technology College, Guangxi, China (LZRVTC), led by the Director, Scientific & Technical Graphic Information, Professor Dr. Zhou Lan, to Universiti Malaysia Pahang (UMP) recently provided an opportunity for both parties to leverage collaborative opportunities in the field of Engineering and Railway Technology.